Medinas Health : building a medical equipment marketplace - Moore, Don A., 1970-; Barton, Marieshka; Girling, Robert Henriques (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2020)
This case centers on the startup Medinas Health, a technology company based in Berkeley, California that aimed to increase the efficiency of the medical equipment market in the U.S. Chloe Alpert, Medinas Health's CEO, envisioned a more sustainable healthcare industry and aimed to reduce waste and improve the financial bottom-line of hospitals. These goals led her to create a digital marketplace to help hospitals manage the sale and acquisition of used medical equipment. An active secondary market would reduce waste by putting used equipment to use and keeping it out of waste dumps. It could also improve a hospital's financial bottom-line by enabling them to recover money by selling their used equipment. If Medinas Health could match surplus equipment to customer demand, they would simultaneously provide cost savings for all parties and reduce the volume of medical equipment entering the waste stream. Their challenge was to make it easy and convenient for medical facilities to promote reuse of medical equipment and to sell their surplus to other medical entities.
Originally Published InMoore, D., Barton, M. & Girling, R. (2020). Medinas Health: Building a Medical Equipment Marketplace. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Medical instruments and apparatus industry -- Case studies; Sustainability -- Case studies